2004
DOI: 10.1074/jbc.m400142200
|View full text |Cite
|
Sign up to set email alerts
|

Primer Utilization by DNA Polymerase α-Primase Is Influenced by Its Interaction with Mcm10p

Abstract: Models of DNA replication in yeast andMuch progress has been made identifying proteins that assemble during early stages in replication prior to the start of DNA synthesis. These events are directed by origins of replication, which orchestrate formation of the pre-replication complex (pre-RC) 1 at origins during the G 1 phase of the cell cycle. They include origin binding by the origin recognition complex and subsequent recruitment of Cdc6 and Cdt1, followed by the loading of the Mcm2-7 complex (1, 2). Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
80
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 40 publications
7
80
0
Order By: Relevance
“…Consistent with this hypothesis, we have recently reported that the core of Mcm10 in S. cerevisiae contains an OB-fold domain , which mediates binding to ssDNA (Fien et al, 2004). This OB-fold domain is evolutionarily conserved, and it could allow human Mcm10 to bind to the lagging stand template, facilitating Okazaki fragment initiation by pol-␣/primase.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Consistent with this hypothesis, we have recently reported that the core of Mcm10 in S. cerevisiae contains an OB-fold domain , which mediates binding to ssDNA (Fien et al, 2004). This OB-fold domain is evolutionarily conserved, and it could allow human Mcm10 to bind to the lagging stand template, facilitating Okazaki fragment initiation by pol-␣/primase.…”
Section: Discussionsupporting
confidence: 50%
“…Our data support the idea that pol-␣ is in a complex with Mcm10 ( Figure 5). Therefor, it is conceivable that Mcm10 interacts directly with the catalytic subunit, as shown for S. pombe Mcm10 (Fien et al, 2004). In budding yeast, a hydrophobic stretch similar to a domain in the mobile loop of Hsp10 is required to stabilize the catalytic subunit of pol-␣, Cdc17/Pol1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a critical interaction during replication because pol ␣ is the only enzyme in eukaryotic cells that is capable of initiating DNA synthesis de novo. Indeed, Mcm10 stimulates the polymerase activity of pol ␣ in vitro (28), and interestingly, the fission yeast Mcm10, but not Xenopus Mcm10, has been shown to exhibit primase activity (29,30). Mcm10 is composed of three domains, the N-terminal (NTD), internal (ID), and C-terminal (CTD) domains (29).…”
mentioning
confidence: 99%